Collective and collaborative drawing in contemporary practice : drawing conversations - Journeaux, Jill (Cambridge Scholars Publishing, 2017)
Whilst both collective and collaborative drawing is being widely explored internationally, both within and beyond educational institutions, there is surprisingly little serious research published on the topic. This realisation led to the first international Drawing Conversations Symposium, accompanied by the Drawn Conversations Exhibition at Coventry University, UK, in December 2015. The two events drew a strong and global response, and brought together a wide range of participants, including academics, artists, researchers, designers, architects and doctoral students. This book considers what.